A City Wide Assessment of the Financial Benefits of Rainwater Harvesting in Mexico City. (8th January 2020) - Concha Larrauri, Paulina; Campos Gutierrez, Juan Pablo; Lall, Upmanu; Ennenbach, Mounir
Abstract: We assess the potential financial benefits of rooftop rainwater harvesting (RWH) in Mexico City from the perspective of property owners and entrepreneurs. A bottom‐up approach was followed by evaluating RWH at individual buildings and aggregating the results to a borough/city level. We consider sector‐specific water demands, potable and nonpotable uses, and user‐specific water tariffs. We find that RWH is economically most beneficial for nondomestic users rather than for small domestic users, who are often the target of RWH interventions. Based on a net present value analysis, a potable RWH system is not favored for most domestic users under the current subsidized municipal water tariff structure. Our analysis only considers capital and maintenance expenses, and not other benefits related to increased access to water and reliability, or social benefits from a switch to a RWH system. If the initial capital expense for RWH is partly financed by transferring the water subsidy to an entrepreneur, then RWH becomes financially attractive for a wide range of domestic users. To improve water access in Mexico City, RWH is attractive in the most marginalized boroughs where water use is currently lower and precipitation is higher. For domestic users relying on trucked water, RWH can have great financial benefits. Our approach provides quantitative data with high spatial specificity, highlighting the places and types of users that would benefit most from RWH. Abstract : Research Impact Statement : Rainwater harvesting has high financial benefits for the commercial sector in Mexico City, but municipal water subsidies need to be re‐targeted for favorable potable domestic use results.